THE EFFECT OF MAQĀṢID-BASED DEVELOPMENT VARIABLES ON ECONOMIC GROWTH BASED ON UMER CHAPRA’S PERSPECTIVE (CASE STUDY: NINE SELECTED OIC COUNTRIES) - salman al parisi; Nurizal Ismail; Indra . (Tazkia Islamic Finance and Business Review, 2015)
Objectives: Human Development Index (HDI) has multidimensional aspects of life. In fact, HDI measures only physical aspects that are needed by human such as education, health and wealth. Accordingly, discussing on human must cover material, physical and spiritual aspects. Maqāṣid is needed as a wasilah (medium) to promote the benefit of human (maslahat), which contains of daruriyyat, hajiyat and tahsiniyat. By then, this study aims to analyze maqāṣid based development variables of Umer Chapra perspective on economic growth in 9 selected OIC member countries.Method: The methodology of the study used mixed methods: qualitative and quantitative. The quantitative applies panel data regression analysis with 9 selected OIC countries (Indonesia, Jordan, Kazakhstan, Kyrgyzstan, Mesir, Pakistan, Togo, Turkey and Uzbekistan) with time series from 2004 to 2013. For qualitative applies content analysis approach by using tafsir of Ibnu Katsir.Results: The finding shows that all independent variables, which are literacy rate, enrollment of school, poverty rate, gini index, life expectancy at birth, rule of law and voice accountability have significant effect on economic growth in 9 selected OIC member countries, both simultaneously and individually.Conclusion: This study concludes that HDI which is bounded by maqāṣid approach affects on increasing of economic growth in 9 of OIC member countries significantly.